2020
DOI: 10.1155/2020/8845262
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Stem Cells Alleviate Cold Allodynia in a Rat Spinal Nerve Ligation Model of Neuropathic Pain

Abstract: Neuropathic pain caused by lesions or nervous system dysfunction is a neuroimmune disease with limited therapeutic options. Adipose tissue-derived stem cells (ASCs) are multipotent mesenchymal stem cells with potent immunosuppressive properties, and their use as novel cell-based therapeutics have been proposed in many immune diseases. However, the analgesic effect and efficacy of ASCs to treat neuropathic pain remain unclear. This study, thus, investigated whether ASCs or ASC-derived culture medium can relieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although there is a tendency for the transplanted cells to homing to the damaged nerve site, there have been reports that intravenous transplanted cells might be trapped in the lungs, which can cause damage to the transplanted cells and is not conducive to the effect of NP relief (Liu et al, 2017). Intrathecal injection is less damaging than direct targeted injection at the injury site, and the limited intrathecal space and the protection offered by the blood-spinal cord barrier permit a smaller amount of cell fluid to arrive at an effective therapeutic concentration for NP after the intrathecal transplantation (Jwa et al, 2020). With NP due to nerve injury, different grafting modalities may be used for accomplishing optimal effect by taking onto account the differences in the structures surrounding peripheral nerves and central nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a tendency for the transplanted cells to homing to the damaged nerve site, there have been reports that intravenous transplanted cells might be trapped in the lungs, which can cause damage to the transplanted cells and is not conducive to the effect of NP relief (Liu et al, 2017). Intrathecal injection is less damaging than direct targeted injection at the injury site, and the limited intrathecal space and the protection offered by the blood-spinal cord barrier permit a smaller amount of cell fluid to arrive at an effective therapeutic concentration for NP after the intrathecal transplantation (Jwa et al, 2020). With NP due to nerve injury, different grafting modalities may be used for accomplishing optimal effect by taking onto account the differences in the structures surrounding peripheral nerves and central nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells are abundant in source and easy to expand, do not express the major histocompatibility complex class II cell surface receptor HLA-DR, and are characterized by low immunogenicity, high immunomodulation and good phenotypic stability. As a result, they can be used for the treatment of diseases involving neuroinflammatory components, such as immune diseases, NP, etc (Franchi et al, 2014;Jwa et al, 2020) A great number of animal experiments have demonstrated that MSCs have great potential to be used for alleviating NP symptoms, such as allodynia and hyperalgesia. Moreover, most of the trials did not observe MSCs-related adverse reactions (Wang et al, 2020).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Various treatments may also differentially affect these two types of allodynia. Intrathecal injection of adipose tissue-derived stem cells in rats selectively reduces cold, but not mechanical, allodynia following L5 spinal nerve ligation ( Jwa et al, 2020 ). On the contrary, electrical stimulation of the spinal cord of SNI rats was found to reduce injury-induced mechanical allodynia without affecting cold allodynia ( Tao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as carbamazepine, gabapentin, felbamate and pregabalin have been studied [ 47 ]. Recently, adipose tissue-derived stem cells demonstrated effective action against the cold allodynia in a rat SNL model [ 48 ]. Similarly, the method was used for the purpose of a deeper understanding of the pathophysiology of the phenomenon: for example, the redistribution of sodium channels in undamaged axons [ 49 ].…”
Section: Animal Models Of Neuropathic Painmentioning
confidence: 99%